An integration mechanism between regulatory agencies to reduce financial and administrative corruption in Iraqi state institutions - Haider Ali Jarad Masoudi; Asaad Mohammed Ali Wahab Awad (Iraqi Journal for Administrative Sciences, 2024)
Integration Mechanism between SAIs to Reduction the Financial And Administrative Corruption in the Iraqi State Institutions. Targeting research studying the reality of the work of the SAIs in Iraq and the extent of coordination between its efforts to curb corruption in the Iraqi state institutions that seemed clear from the authorities and bodies concerned with transparency international and local reports, the research aims to suggest a mechanism possible application it aims achieve a kind of integration and coordination between these multiple devices and to ensure the effective and efficient performance to curb the rampant corruption in state institutions, Through the study of the reality of Iraqi SAIs, The research found that the lack of a clear mechanism for coordination between SAIs led to the poor performance of these SAIs agencies in carrying out its functions to the fight against corruption , as well as not to include the relevant laws of a clear mechanism of coordination between SAIs and the ineffectiveness and weakness of each of provincial councils and offices of inspectors general in the fight against financial and administrative corruption on its role as defined constitutionally and legally. The fight against corruption is no doubt require the concerted efforts of all of the judicial, legislative and regulatory bodies, and this will not be without a mechanism for effective coordination with each other to achieve the purpose of its existence, but the multiplicity of regulatory agencies without a clear mechanism for the coordination of the perpetrator of these devices makes them useless. The research provides a regulatory mechanism for regulatory agencies aim to achieve the integration of these devices work through effective coordination among themselves within the roadmap for the smooth flow of complaints of the complainant, The research reached a proposed mechanism of the organizational structure of the control devices and the coordination mechanism effectively with each other through a streamlined complaint from the actors complainant map through related devices , as well as integrate the offices of general inspectors with the audit and internal control departments in ministries and formations one device called the (internal Control and Inspection Department) FBSA) and associated ) and recommendation to amend Federal Board of Supreme Audit.